Restoring free speech and liberty on campus - Downs, Donald Alexander (Cambridge University, 2013)
This book addresses a major problem in contemporary American higher education: deprivations of free speech, due process, and other basic civil liberties in the name of favored political causes. Downs begins by analyzing the nature and evolution of the problem, and discusses how these betrayals of liberty have harmed the truth seeking mission of universities. Rather than promoting equal respect and tolerance of diversity, policies restricting academic freedom and civil liberty have proved divisive, and have compromised the robust exchange of ideas that is a necessary condition of a meaningful education. Drawing on personal experience as well as research, Downs presents four case studies that illustrate the difference that conscientious political resistance and mobilization of faculty and students can make. Such movements have brought about unexpected success in renewing the principles of free speech, academic freedom, and civil liberty at universities where they have been active. [from publisher description].